Ontogenetic development of inner ear hair cell organization in the New Zealand carpet shark Cephaloscyllium isabellum - Sauer, Derek J.; Yopak, Kara E.; Radford, Craig A. (Frontiers in Ecology and Evolution, 2022)
The inner ear hair cells of fishes can provide insight into the early evolution of vertebrate inner ear structure. The same basic structure, the sensory hair cell, provides the fundament for auditory and vestibular function in jawed vertebrates, and fishes represent some of the first vertebrates to evolve auditory capacity. Despite holding critical basal position in the evolutionary tree of gnathostomes, relatively little is known about inner ear hair cells in elasmobranchs. Specifically, the extent of plasticity in hair cell organization throughout ontogeny among different sensory epithelia and the degree of variation between species is unknown. In this study, we characterized the inner ear hair cells of the New Zealand carpet shark Cephaloscyllium isabellum throughout ontogeny by quantifying macular area, number of hair cells, hair cell density, and hair cell orientations in the inner ear maculae from a range of body sizes. Similar to other elasmobranchs and bony fishes, macular area and the number of hair cells increased throughout ontogeny in the otolith organs. The orientations of hair cells within each maculae also was consistent with the limited data on other elasmobranchs. However, contrary to expectation, the macula neglecta did not increase in area or hair cell number throughout ontogeny, and hair cell density did not change with body size in any maculae. These findings suggest there may be variation between elasmobranch species in ontogenetic development of hair cell organization that may be related to hearing capabilities throughout life.